UNVEILING URBAN ENTREPRENEURSHIP: CHALLENGES AND DEMOGRAPHICS OF STREET VENDORS IN UDAIPUR CITY - Dr. Sachin Gupta, Dr. Vijayendra Gupta, Dr. Priya Sachdeva, Charchil Kumar Jain, Chetna Kaushik (Chelonian Research Foundation, 2022)
Street vendors, individuals selling goods without a permanent storefront, have become ubiquitous in major cities, particularly in emerging nations. This rise is driven by rural-to-urban migration for economic opportunities and the pressure on those with formal sector experience to join the informal sector due to closures or downsizing. This research explores the challenges faced by street vendors in the Udaipur region, shedding light on the multifaceted nature of their entrepreneurial endeavors. The study encompasses a demographic analysis of 510 street vendors, revealing the diverse educational backgrounds and essential role they play in providing goods to urban communities. Hypothesis testing confirms the existence of significant challenges, while an in-depth examination of 31 specific issues showcases the complexity of their entrepreneurial journey. Factor analysis further elucidates the underlying components influencing these challenges. The findings contribute valuable insights to both academic discourse and practical considerations for policymakers and urban planners seeking to support and integrate this crucial segment of micro-entrepreneurs into the urban landscape. Keywords: -Street Vendors, Entrepreneurial Challenges, Urban Micro-entrepreneurs, Demographic Analysis and Factor Analysis etc